Crystal-plane-dependent metal–support interaction in Au/TiO21. Issue 7 (21st February 2015) - Liu, Lichen; Ge, Chengyan; Zou, Weixin; Gu, Xianrui; Gao, Fei; Dong, Lin
<x xml:space="preserve">Abstract</x> The metal–support interactions between Au and different TiO2 crystal planes are investigated to identify their crystal-plane-dependent properties.